Optimization of Age at Maturity in Surti Buffalo Heifers with Dietary Supplementation of Bypass Protein and Bypass Fat - Sarvaiya, Nitesh P; Parmar, Abhishek B; Parmar, Ajay P; Patel, Dilip C (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Surti buffaloes heifers reared under ideal feeding and managemental practices achieve puberty, sexual maturity and first calving at  the optimum desired age and body weight. In growing heifers during first parity, requirement of high plane of nutrition is obvious to  meet the demands of body growth of dam, growth of fetus, and galactopoetic functions. This study was aimed to find out the effect of  feeding bypass protein and bypass fat right from the age of puberty up to the age of first successful conception, i.e. maturity in Surti  buffalo heifers. Sixteen Surti buffalo heifers were allotted in four equal groups (n=4 in each group), viz., Control (T-1) fed basal diet  following ICAR nutrient requirements, T-2 basal diet + 30 % protein of concentrate mixture replaced with formaldehyde treated guar  meal (FTGM), T-3 basal diet + 100 gm bypass fat (BF), and T-4 basal diet + 30 % protein of concentrate mixture replaced with FTGM  + 100 gm of BF. All the treatment diets were isonitrogenous. The results revealed that there was beneficial effect of feeding by pass  protein and bypass fat along with routine feeding management on growth of heifers in terms of the body wt. gain and reduced age at  first conception (maturity) and thereby age at first calving (AFC). AFC reduced to 37.25, 37.87 and 33.37 months, respectively, in T2, T3  and T4 groups respectively; compared to 43.75 months in Control group. Further, the net benefit over control, in the group of heifers fed with FTGM alone and FTGM plus BF groups were 22.90 % and 16.40 % respectively.
Keywords: ge at first calving; Bypass fat; Formaldehyde treated guar meal; Maturity; Surti buffalo